Mechanization Taro Chips Processing at Small Micro Medium Enterprise in Tambakan village, Blitar District - Lilik Suprianti; Hervina Puspitosari; Alfian Chandra Ayuswantana; Rida Perwita Sari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The community service program to assist the Small Micro Medium Enterprise in Tambakan Village, Blitar Regency East Java, has been done. The program's purpose was to improve the productivity of Taro chips as the prime product of Berkah Mulya Small Micro Medium Enterprise by introducing the appropriate technology to the taro chips making process. Currently, taro chips are produced manually. People did all the steps from cutting, frying, oil separating, and packaging by hand. It was time-consuming. The products sometimes were not uniform in thickness beside the oil content was relatively high, so the product was easy to be rancid. We introduced the cutting machine and the spinner to improve Taro Chips production's quality and quantity in this program. The methods used in this program started with a field survey, observation, socialization, the introduction of the appropriate technology (cutting and spinner machine), workshop and training, and evaluation. By applying the technology, the productivity increased from 5 kg/ day become 25 kg/day. The product's quality also becomes uniform in thickness, and the expiration date becomes longer